ANALISIS KINERJA PERUSAHAAN PERBANKAN SEBELUM DAN SESUDAH MENJADI PERUSAHAAN PUBLIK DI BURSA EFEK JAKARTA (BEJ) - Yuli, Astuti (Fakultas Bisnis UKDW, 2006)
Go pubtic is selling.stock or o company obligation to the public in the stock market, in which by Initial Public ffiring QPO). Go pubtic compay will receive fund or cash, therefore it is expected that the company prospect ningt get better throught the expasio, which is doheIn this research, it is doe empiris study to is public bank sample. He sample are take by purposive sampling fr.om 2l banlcs listed on BEJ. History list are got. from the bank Jinancial report approximate years of age lasted o 3l December. We hope that the study result can give answer the questioh